'Pseudo-Ancient Woodland' and the Ancient Woodland Inventory. (November 2013) - Stone, Adam; Williamson, Tom
Abstract : The concept of a distinct class of 'ancient woodland' is often accepted in an unproblematic manner by landscape historians. Woods so defined have been managed in traditional ways, have supposedly been in existence since before c. 1600, and today feature a distinctive range of 'indicator' species. This article argues that a significant number of the woods officially defined as 'ancient' are in reality of comparatively recent origin despite displaying most, if not all, of the features usually considered to be indicative of ancient woodland. The defining aspects of 'ancient' woods may result as much from their landscape context as from their antiquity per se.